The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1177/1420326x20935279
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort under weightlessness: A physiological prediction

Abstract: This study investigated the physiological thermal response of people under simulated weightlessness using a 6° head down bed rest (HDBR) model to ensure the human body functions in the weightlessness way. Thermal responses of six male participants were experimentally determined. The relationship between thermal comfort and heart rate variability (HRV) was also scrutinized. Physiological responses of participants under different environmental conditions were observed including core temperature, sweating, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Regarding the risk of bias due to deviations from the intended interventions, three studies (Brenner et al 1997, Yamamoto et al 2007, Zhu et al 2020 with a small sample size (n 8) did not report statistical power data or sample size calculations. Concerning the missing outcome data, no articles were ranked as 'high risk'.…”
Section: Risk Of Bias and Quality Of The Studiesmentioning
confidence: 99%
“…Regarding the risk of bias due to deviations from the intended interventions, three studies (Brenner et al 1997, Yamamoto et al 2007, Zhu et al 2020 with a small sample size (n 8) did not report statistical power data or sample size calculations. Concerning the missing outcome data, no articles were ranked as 'high risk'.…”
Section: Risk Of Bias and Quality Of The Studiesmentioning
confidence: 99%
“…Therefore, many scholars have improved some environmental parameters on the basis of standard ones to meet the needs of extreme environments [8][9][10][11][12][13] or specific functions. 1,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Table 1 summarizes the features of some environmental chambers.…”
Section: Introduction To Environmental Chambersmentioning
confidence: 99%
“…hospital patients, elderly, children and pregnant women). [7][8][9][10][11][12] Multiple studies on the thermal comfort of sensitive populations (such as patients, the elderly and children) have been published in recent years (see Table 1 for details). These studies have reported differences between the predicted neutral values and the actual neutral values.…”
Section: Introductionmentioning
confidence: 99%